The Cost of the Social Welfare System as an Investment in Human Capital in Poland - Litwiński, Michał (Studia Oeconomica Posnaniensia, 2017)
Human capital is an important factor of socio-economic development. Among the factors that have an influence on the volume of the resource there is an underestimation of the meaning of costs from the social welfare system. The paper looks into the concerns that influence social welfare costs on the level of human capital. The aim of the paper is to verify the hypothesis that the cost of the social welfare system could be invested in the development of a resource in Poland. The aim of the paper is an attempt at changing the perception of the social welfare system. The research carried out in the paper could also be justification for the implementation of long-term strategies. Moreover, investment in human capital are crucial regarding demographical changes (especially of an aging population) - planning expenditures from the social welfare system in a way supporting the development of the resource considered could decrease the burden of the system in the future (e.g. taking care of the health of people at a productive age could diminish the cost of health care in the future). A basis of the research is the literature review. Conclusions were formulated on the basis of an econometric analysis of data from Poland in the period 2003-2013. The quantitative research regards a correlation analysis, the Granger causality test, the VAR model and an impulse-response analysis.